Pollutant Load Capacity of Rawa Besar Lake, Depok, West Java - Junita, Alfira; Hendrawan, Diana Irvindiaty; Kusumadewi, Riana Ayu; Aphirta, Sarah (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
Depok City has dozens of lakes and one of them is Lake Rawa Besar. The Depok government gives priority to Rawa Besar Lake to be development as a tourist destination. At this time the waters of Rawa Besar Lake are in a polluted condition caused by domestic waste, land use change, chicken farming and floating net caramba. The study aims to analyze water quality, determine the carrying capacity of pollutant loads and provide recommendations for pollutant load reduction. The calculation of the Pollution Load Capacity refers to Minister of Environment Regulation No. 28 of 2009. Based on water quality analysis, 5 parameters exceed the quality standard, such as BOD, COD, total phosphate, total nitrogen, and total coliform. Using the model and calculation of the pollutant load capacity of lake and/or reservoir. The pollutant load capacity of Lake Rawa Besar for BOD parameters is 50.26 kg/year while the existing load is 262.76 kg/year, COD is 418.81 kg/year existing load is 1150.41 kg/year, phosphate is 0.50 kg/year existing load 26.45 kg/year, nitrogen 12.56 kg/year existing load 85.88 kg/year and total coliform 8.4 x 104 amount/year existing load 9.6x106 amount/year. The burden of incoming pollutants exceeds the pollutant load capacity of Lake Rawa Besar. Pollution control efforts are carried out by implementing communal wastewater treatment systems such as an Anaerobic Baffled Reactor (ABR).